AN ASSESMENT OF THE IMPACT OF COVID 19 ON FUEL PRICES AND THE SALES PERFORMANCE OF PETROL STATIONS IN UGANDA - Nangendo Tracy Jean (Uganda Christian University, 2024)
This research is about “An Assessment of The Impact of Covid 19 On Fuel Prices and The Sales Performance of Petrol Stations in Uganda”, with a specific focus on the central region of Uganda. The study aims to investigate the economic and social effects of Covid 19 on local residents, as well as the Fuel Prices and The Sales Performance of Petrol Stations. Chapter 1 includes the background of study, problem statement, objectives of the study; To identify the effects of COVID19 on Uganda, to assess the effect of COVID-19 on fuel prices and to examine the relationship between fuel prices and sales performance, research questions, purpose of the study, significance of the study, scope of the study and the conceptual framework. Chapter two is about the theoretical review from other authors entailing the endogenous growth theory and reviewing all specific objectives. Chapter three is about the methodology deployed that is the research design, area of study, the study population, sample size and technique and the instruments of data collection. Whereas chapter four and five is about the analysis of data, presentations of data, the discussions and recommendations. Using a mixed-methods approach, combining both qualitative and quantitative data collection and analysis methods, this research reveals that COVID 19 had both positive and negative impacts on local communities. While some benefits, such as incorporating new technologies e.g. working online and infrastructure development, have been realized, concerns around fuel prices, laying off workers, and inadequate compensation remain. The study concludes by providing valuable insights into the impact of COVID-19 on the fuel industry in Uganda, specifically on fuel prices and petrol stations' sales performance. The findings will help petrol stations and policymakers develop strategies to mitigate the impact of future pandemics on the fuel industry.
Dissertation Bacherlor's